Review Article: Antibacterial Activity of Mangrove Lindur Extract (Bruguiera gymnorrhiza) Against Staphylococcus aureus - Setyadi, Yudha Putra; Kurniawaty, Evi; Kusumaningtyas, Intan (CV. Jasa Sukses Abadi, 2024)
Infectious diseases remain prevalent in Indonesia, influenced by environmental factors such as poor sanitation, low public awareness of clean and healthy living behaviors, and a tropical climate. Infectious diseases are health issues caused by microorganisms, such as bacteria, viruses, or parasites, that enter the body. Staphylococcus aureus is one of the primary pathogens for humans and can cause various infections. The main treatment for Staphylococcus aureus infections is antibiotics. However, bacterial resistance to methicillin antibiotics (Methicillin-Resistant Staphylococcus aureus or MRSA) is increasingly common in Indonesia. Therefore, alternative antibiotic treatments based on plant-derived compounds are highly needed. One plant with potential antibacterial activity is Bruguiera gymnorrhiza. Commonly known as bakau lindur, various parts of Bruguiera gymnorrhiza, such as its bark, leaves, and roots, have antibacterial properties. This is attributed to the bioactive compounds present in its extracts, including flavonoids, saponins, alkaloids, phenols, steroids, terpenoids, and tannins.. This article aims to determine whether Bruguiera gymnorrhiza extract exhibits antibacterial activity against Staphylococcus aureus. Based on the literature review, Bruguiera gymnorrhiza extract has been proven to possess antibacterial activity against Staphylococcus aureus. The best antibacterial activity was observed in the 96% ethanol extract of Bruguiera gymnorrhiza bark at a concentration of 15,000 ppm, resulting in a 13.62 mm inhibition zone categorized as strong.